Ruminal acidosis in local bucks fed on al-zahdydates: Laiby.A.K. , AL-Samarrae , S.A.G. AL-Kinani, L.M.Z. - K., Laiby A. (The Iraqi Journal of Veterinary Medicine, 2006)
Ruminal acidosis was induced experimentally in local bucks fed onAL-zahdy dates at 20 and 40 g/kg B.W. daily. Two groups of five animalseach beside another group of five animals as a control reseved 20g/kg B.W.of concentrates beside green roughage. One animal from each group wassurgically provided with ruminal fistula. The experiments lasted for fourweeks during which the animals examined clinically daily, and ruminal fluidand blood samples were collected weekly.The results showed that theanimals in the two experimental groups show significant rise in the means ofrespiratory and pulse rates,but not in body temperature.The ruminalcontractions ranged between weak and reduced in the 1st experiment totemporary loss of contractions in the 2nd experiment. All experimental goatsmanifested weakness, depression, loss of appetite, however, temporaryrecumbency was noticed in the goats of the 2nd experiment. The color of theruminal fluid was light to dark green in the control group while theexperimental groups showed light to dark brown color .The pH reached it’slowest levels, and the number and activity of the microflor altered afteramount of feeding on dates in the experimental groups to become reduced ordead after six and five hours respectively. The positive to negative bacterialratio changed in the experimental groups. The level of volatile fatty acids,lactic acid concentrations and ammonia nitrogen in the rumen increased.Also the experimental animals showed biochemical changes in all bloodparameters. Feeding of bucks on 20 g/kg B.W.of Al-Zahdy dates dailycaused a simple form of ruminal acidosis, while 40 g/kg B.W.of dates dailycaused the subacute form of acidosis.